DEIKSIS DALAM PIDATO PEMBINA UPACARA DI SD NEGERI SIDOREJO SEBAGAI BAHAN AJAR MATERI PIDATO KELAS IX (KAJIAN PRAGMATIK) - Ellie Natanael Kurnia Agung; Dyah Wijayawati; Etin Pujihastuti (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
Pragmatics is a study that examines the meaning of speech based on the speech context. One of the studies is deixis. This research is motivated by the misconceptions on the use of nearly similar deixis in some public speech,which are often confused or considered to be same. Example is in the form of spontaneous speech. The purpose of this research is to describe the types and meanings of deixis contained in the speech of the ceremonial inspector at SD Negeri Sidorejo by using study of pragmatics studies and its use as a reference for teaching material in junior high school. The data in this study are ceremony inspector’s speech fragments containing deixis. Collecting data using the observation method with basic tapping techniques to record the ceremony inspector’s speech and the advanced techniques of note to convert the recorded to written form and collecting deixis in it. The data analysis technique used was qualitative data analysis, the equivalent method with the basic technique of Dividing Key Factors Technique to describe the types and meanings of deixis in the speech of the ceremonial supervisor. The result shows that the types of deixis found were matched with Yule’s theory, that is persona deixis (99 data), place deixis (26 data), and time deixis (24 data). The results can be used as a reference for Indonesian Class IX Basic Competence 3.3. Identifying ideas, thoughts, views, directions or messages in a persuasive speech about actual problems heard and read, and Basic Competence 3.4 Examining the structure and characteristics of persuasive speech about actual problems that are heard and read.